AB0082 Clinically relevant discrepancies between different rheumatoid factor assays. (12th June 2018) - Falkenburg, W.; von Richthofen, H.; Koers, J.; Weykamp, C.; Schreurs, M.; Bakker-Jonges, L.; Haagen, I.-A.; Lems, W.; Hamann, D.; van Schaardenburg, D.; Rispens, T.
Abstract : Background: Accurate measurements of rheumatoid factors (RFs), autoantibodies binding IgG, are important for diagnosing rheumatoid arthritis (RA) and for predicting disease course. Worldwide, various RF assays are being used that differ in technique and target antigens. Objectives: To study whether assay choice leads to clinically important discrepancies in RF status and level. Methods: RF measurements using 4 commercial RF assays were compared in 32 RF + samples. Using ELISAs, the influence of the target antigen source—human IgG (hIgG) versus rabbit IgG (rIgG)—on measured RF levels was investigated in arthralgia patients and RA patients. Results: Substantial discrepancies were found between RF levels measured in the four commercial assays. 6 samples (19%) with RF levels below or slightly above the cut-off in an rIgG-based assay were RF + in three assays using hIgG as the target antigen, some with very high levels. Direct ELISA comparisons of RF reactivity against hIgG and rIgG estimated that among 173 ACPA + arthralgia patients, originally RF negative in rIgG-based assays, up to 10% were single positive against hIgG. Monoclonal RFs binding to hIgG and rIgG or hIgG only supported these findings. In a cohort of 69 early RA patients, virtually all RF responses reacted with both targets, although levels were still variable. Conclusions: The use of RF assays that differ in technique and target antigen, together with the different specificities of RF responses, leads to discrepancies in RF status and levels. This has important consequences for patient care if RA diagnosis and disease progression assessments are based on RF test results. Disclosure of Interest: None declared